Factors Influencing on-line Game Addiction of Children (Medico Legal Update, 2020)
Background/Objectives: The purpose of this study was to investigate factors contributing to on-line game addiction in 3rd, 4th, 5th, 6th graders living in 2 cities of korea.Method/Statistical Analysis: This study applied cross-sectional research design with a structured questionnaire. The subjects were 381 elementary school students in Korea. Data were collected after describing the purpose and contents to the students and were analyzed using SPSS 25.0 program.Findings: The relative influence toward the children’s ego-resilience was shown in the order of importance as follows; trait anxiety, gender, internet time of use, perceived home atmosphere, and satisfaction with school life.Improvements/Applications: From the study, on-line game addiction appeared to be influenced by multiple factors such as gender, perceived atmosphere, satisfaction of school life, Internet time of use and trait anxiety and These variables should be considered when developing nursing interventions for online game addiction.